The Role of FBI Counterintelligence Program in Disrupting Activism of the Nation of Islam and other African-American Political Movements in the USA - Zeghoudi, Yahia (The Algerian Historical Journal, 2026)
In this article we sought to examine the interference of the Federal Bureau of Investigation (FBI) in African Americans' activism for justice, equality and a racism-free society in the USA. We found out that the FBI interfered in this activism since the early 20th century by surveilling their political activities, infiltrating agents to spy on their leaders, creating tension among them, using the mass media to distort their image, using justice to imprison them by finding excuses to imprison leaders and followers, breaking their political parties and even inciting some leaders to commit suicide or assassinating them. This happened with the Moorish Science Temple of America, UNIA, NOI and all other black movements. We used historical as well as declassified FBI files analysis to reach these results. The research is important for researchers interested in the subject of the NOI mainly and African American activism in general.